Anatoly Alexandrovich Lobenko - Odessa State Medical University, Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The article deals with the 75th birthday of a famous scientist in the field of orthopaedic traumatology and marine medicine A.A. Lobenko.